Zur Verbreitung der Arten der Formica rufa Linnaeus-Gruppe. II. Die hügelbauenden Formica-Arten in der Sozialistischen Republik Rumänien (Hymenoptera: Formicidae). - Otto, Dieter; Paraschivescu, D. (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The hill-building wood-ants from 68 collecting-places in Roumania were determined. The species-group of Formica pratensis Retzius, F. nigricans Emery strongly predominated. F. polyctena Foerster and F. rufa Linnaeus as well as F. truncorum Fabricius are to be found in a small number of nests in the middle altitude of the mountains. In the high mountains F. (Raptiformica) sanguinea Latreille prevails, which is found in all other wood districts too. F. lugubris Zetterstedt and F. aquilonia Yarrow are absent. F. (Coptoformica) exsecta Nylander was discovered only in one place.